Participation Non-Governmental Organization In Protecting Child Rights In The Area Of Social Conflict (Ushuluddin International Conference (USICON), 2017)
Children are the next generation, this cannot be denied. Rights of the child in any State, always protected and always maintained. Indonesia as a State law also recognizes the protection and guarantee of children's rights. On this day the child's protection seems to be ignored or even forgotten. In the case of social conflicts in conflict-prone areas, the rights of children are ignored (education rights, health rights, welfare rights and other rights). Above this article tries to discuss: 1) what is the condition of the child in case of social conflict in Indonesia? 2) how does the state ensure sustainable child protection, in case of social conflict in Indonesia? 3) and initiate sustainable child protection. This research uses normative juridical research. The current condition of children in Indonesia is categorized as protection extraordinary, especially if there is social conflict in Indonesia. States should ensure continuous protection of children in the event of social conflict in Indonesia, in order to provide legal certainty to the protection of children's rights, so that children will be protected by their rights. We must not turn a blind eye to the enforcement of child protection laws. The idea of ??sustainable child protection is our common goal, but it must be remembered that all parties must be active to realize child protection, it is very important to build the next generation of good nation.
Keywords: Participation; Non-governmental organization; Child; Social conflict